PENERAPAN METODE KITABAH DALAM MENINGKATKAN KUALITAS HAFALAN AL-QUR'AN JUZ 30 MATA PELAJARAN PAI DI SMA NEGERI 18 MAKASSAR - Rabbani, Ahmad; Nurlaelah; Nengsih, Ratika; Surani; Subaedah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of the kitabah method in improving students' Al-Qur'an memorization quality in the Islamic Education subject for class XII.1 at SMA Negeri 18 Makassar. This research employed Classroom Action Research (CAR) conducted in two cycles, where each cycle consisted of planning, action, observation, and reflection stages. The subjects of this study were 31students. Data collection techniques used were observation, documentation, and oral tests. The results showed that the implementation of the kitabah method improved students' memorization quality. In the pre-cycle stage, classical mastery was only 54% with a class average score of 71. After the intervention in cycle I, the mastery percentage rose to 67% with an average score of 79, and further increased to 87% with a class average score of 89 in cycle II. These improvements indicate that the kitabah method modified using tracing worksheets is effective in creating an active and effective learning process. Thus, it can be concluded that the kitabahmethod is effective in improving students' Al-Qur'an memorization quality in the Islamic Education subject.